Assessing Past and Future Heat and Cold Waves over Iraq Using CMIP6 Model - Abadla, Zaher Al; Ahmed, Mustafa; Aldashti, Hasan; Wahab, Mohamad Magdy Abdel (Iraqi Journal of Science, 2024)
The United Nations classified Iraq as one of the most vulnerable countries to climate change. Temperatures continue to rise leading to more heat waves, droughts, sandstorms, and desertification. This study aims to investigate the characteristics of heat waves over Iraq from 1982 to 2050 using CMIP6 model at RCP4.5 scenarios. The results clearly showed that the effects of climatic changes were evident in the maximum and minimum temperatures inside Iraq. Average temperature increased of 1.9°C between 1982 and 2020. During 1999, there was a sharp increase in summer days for all stations. The annual number of summer days for the stations (Basra, Nasiriyah, Baghdad, Rutba, Sulaymaniyah, and Mosul) was (195, 193, 177, 108, 106, and 142), while in 2039 the number of summer days was found to be (212, 206, 194, 143, 144, and 149), respectively. The increase in the number of discrete heat wave events began in 2020 and will continue until 2050 for almost the entire territory of Iraq. The warmest day in Basra was in July 2016 with 53.2°C, while the projection of the warmest day was found in July 2046 with 55.7°C. The coldest daily temperature reached -5.03 °C for Baghdad in 1997 and -10.1°C for Sulaymaniyah in 1985, while the projection of the coldest day was -16.2°C over Sulaymaniyah in 2039. The trend of the number of days contributing to cold wave events was decreasing for all stations whereas the coldest year for all stations was 1992 for the entire period (1982 to 2020). Heat waves accelerated from the beginning of the study period in 1982 and continued to increase until the end of the study in 2050 in Iraq.